Metabolic-associated steatotic liver disease and risk of Alzheimer’s disease: a real-world retrospective cohort study - Zhang, Jiaqi; Wang, Wenzhao; Hou, Xingyun; Wu, Jia; Wang, Yifan; Fan, Jianling; Zhang, Zhiyu; Yuan, Zhizhong; Sun, Cuifen; Lu, Bin; Zheng, Jiaoyang (Frontiers in Endocrinology, 2024)
Objective: Alzheimer's Disease (AD) is increasingly recognized as being associated with metabolic disorders, including Metabolic Associated Steatotic Liver Disease (MASLD). This study aimed to assess the relative risk of AD in individuals with MASLD.In this retrospective cohort study, we analyzed data from individuals aged over 65 who underwent health check-ups between January 2018 and June 2023. MASLD was diagnosed based on ultrasound findings and cardiometabolic criteria. AD incidence was identified using ICD-10 codes and self-reports. Poisson regression models estimated the relative risk of AD in relation to MASLD, adjusting for age, BMI, sex, SBP, HbA1c, HDL-c, triglycerides, hs-CRP, GGT, and estimated GFR.The study included 4,582 MASLD patients and 6,318 controls. MASLD patients showed a higher incidence of AD (127 cases) compared to controls (61 cases). The fully adjusted Poisson regression model indicated an increased AD risk in MASLD patients (RR: 2.80 (95% CI: 1.79-4.38)).Our findings suggested MASLD as an independent risk factor for AD, underlining the role of metabolic dysfunctions in AD pathogenesis. The study emphasized the need for comprehensive metabolic health management in AD prevention strategies, particularly among high-risk groups.